PENGARUH PEMBERIAN PUPUK BOKASHI DAN NPK (15-15-15) TERHADAP PERTUMBUHAN DAN PRODUKSI BEBERAPA VARIETAS TANAMAN JAGUNG (Zea mays L.) - Amri Putra Sembiring; Mbue Kata Bangun; E. Harso Kardhinata (Universitas Sumatera Utara, 2013)
Corn is the third plant of food after wheat and rice. To increasing of productionneeded to use hybrid and nonhybrid variety, with organic and unorganic fertilizer. Theobjective of this research was to evaluate the influence of bokashi and NPK fertilizer ongrowth and yield some maize varieties.The research was carried out in the UPT Balai BenihInduk Palawija Tanjung Selamat, Deli Serdang. This research used Randomized BlockDesign. Two varieties of maize (Bisma and SHS-4), two levels of bokashi (0 and 180g/plant), and three dosages of NPK (4,2 ; 8,4 ; 16,8 g/plant) were used in the experimentwith three replications. The results showed that varieties were significantly different toparameters plant height and numbers of leaf. Bokashi treatment have no significant effectto all parameters. NPK treatment were significant to parameter numbers of leaf at 6 dan 7week after planted. The combination between varieties and bokashi, varieties dan NPK,bokashi and NPK, and combination of varieties, bokashi and NPK have no significanteffect to all parameters.Key words : Variety, Bokashi, NPK Fertilizer